Specifics of the Latin American world view construction - A. F. Kofman (Ибероамериканские тетради, 2023)
There are two main strategies for a world view formation in a literary work: the first one is direct, when the writer focuses on the national reality itself recreating it as a self-sufficient phenomenon independent of «someone else’s view»; the second one is «reverse». Its main feature is that the world view is formed in the process of a constant comparison with another culture, exploring and evaluating their own culture through the eyes of a foreigner. In Western European literature, the direct strategy is extremely dominant, whereas in Latin American literature, the reverse strategy has acquired the significance it has never had in the European one. It is proved by two ways in which the reverse strategy manifests itself: the first one is «looking outside», that is, the assertion of the uniqueness of Latin American reality through its juxtaposition with the European one; the second one is «looking from outside», which offers the perception of Latin American reality by an «outsider». The question arises: what factors have determined the dominance of the reverse strategy in Latin American literature? One of the reasons is that the latter has evolved by absorbing and processing the European literary patterns: this path of evolution is defined as «the search for one’s own in someone else’s». But this is not the only factor. Since the 16th century, the era of the birth of Latin American culture, the mode of perception of America has been formed as the opposition of the New World to the Old World and contained the motive of amazement at the «miraculous» reality, which was preserved in the genetic memory of culture materializing in the 20th century as magic realism.